2012
DOI: 10.1002/ange.201200078
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Aromatic Azidocarbonylation

Abstract: Aryliodide reagieren mit NaN3 und CO in Gegenwart eines Pd/Xantphos‐Katalysators glatt zu Aroylaziden (ArCON3) in 75–92 % Ausbeute. Die Reaktion läuft unter milden Bedingungen ab (1 atm, 20–50 °C) und ist mit vielen funktionellen Gruppen verträglich. (Xantphos=9,9‐Dimethyl‐4,5‐bis(diphenylphosphanyl)xanthen)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…5d In the study of the Grushin research group, Pd(0)/xantphos was found to catalyze the aromatic azidocarbonylation, and the aroyl azide products did not undergo further Pd-catalyzed carbonylation. 7 Therefore, the observation that Pd(0) species exhibited comparable catalytic activity to Pd(II) prompted us to investigate the reaction mechanism, in particular to figure out the real catalytic species and the pathway of azide activation and carbonylation.…”
Section: ■ Mechanistic Studymentioning
confidence: 99%
“…5d In the study of the Grushin research group, Pd(0)/xantphos was found to catalyze the aromatic azidocarbonylation, and the aroyl azide products did not undergo further Pd-catalyzed carbonylation. 7 Therefore, the observation that Pd(0) species exhibited comparable catalytic activity to Pd(II) prompted us to investigate the reaction mechanism, in particular to figure out the real catalytic species and the pathway of azide activation and carbonylation.…”
Section: ■ Mechanistic Studymentioning
confidence: 99%
“…Besides above carbonylative synthesis of acid fluoride, carbonylations of aryl halides with hydrogen, alcohol, amine, organometallic compound, have been extensively used to produce aldehyde, ester, amide, and ketone 34 . However, some unconventional nucleophiles, such as weakly nucleophilic aromatic amines (especially NH-heteroarenes) 66 , strongly coordianting CN − 67 and intolerable N 3 − 68 have been scarcely used for carbonylative transformation due to their inherent limitations, and corresponding heterogeneous carbonylation procedures have not been reported yet. But nevertheless, the corresponding carbonyl compounds of above nucleophiles are important building blocks in the syntheses of fine chemicals and bioactive compounds 69 71 .…”
Section: Resultsmentioning
confidence: 99%
“…Whenever the fluorescence enhancement stopped, we assumed that the reaction had ended. Upon the addition of 10 μM of MPVC-I to 1 equiv (equiv) of Pd(OAc) 2 and 20 μM of Xantphos in PBS (phosphate buffer saline, 10 mM), the mixture showed weak 557 nm emission upon 424 nm excitation, but in the presence of 200 equiv of azide (azidation did not occur due to the inactive nature of MPVC−Pd-N 3 reductive elimination 32 ), the fluorescence decreased to almost zero. After bubbling 1 atm of CO into the azide-containing system, fluorescence emission was rapidly enhanced by 80−100-fold at 552 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Article azidocarbonylation could proceed rapidly at ambient temper-ature and pressure; 32,33 moreover, the stable acyl azide intermediates were isolated and characterized by single crystallography. Curtius rearrangements usually do not proceed rapidly in the absence of ortho-substituents on aryl iodide, 34 so it is plausible to suspend the azidocarbonylation reaction at a high fluorescent acyl azide stage within the CO detection time scale.…”
Section: Acs Sensorsmentioning
confidence: 99%
See 1 more Smart Citation